Cutaneous T-Cell Lymphoma, a Novel Manifestation of PDGFRA-Rearranged Neoplasm. (August 2018) - Behdad, Amir; Allen, Pamela; Lu, Xinyan; Zhou, Xiaolong Alan; Guitart, Joan; Chen, Qing; Pro, Barbara
Abstract : Abstract: Patients with PDGFRA -rearranged hematopoietic neoplasms typically present with chronic eosinophilic leukemia and rarely with acute myeloid leukemia or T-lymphoblastic lymphoma. However, mature T-cell lymphoma has not been previously associated with PDGFRA aberrations. We report a patient who presented with simultaneous T-lymphoblastic lymphoma, focal myeloid proliferation, and cutaneous cytotoxic T-cell lymphoma refractory to chemotherapy. The presence of myeloid and lymphoid lineages prompted genetic and molecular studies. A PDGFRA rearrangement was identified in all compartments: cutaneous, lymph node, and bone marrow. Treatment with imatinib resulted in an excellent response in cutaneous and systemic disease. We report the first case of a mature cutaneous T-cell lymphoma with PDGFRA rearrangement, expanding the spectrum of neoplasms associated with this genetic abnormality. Our case underscores the great importance of recognizing PDGFRA rearrangement in unusual cases of cutaneous T-cell lymphoma, systemic lymphoid, and myeloid neoplasms. These patients may respond well to tyrosine kinase inhibitors, despite resistance to conventional chemotherapy.